HUBUNGAN FREKUENSI BERMAIN BULU TANGKIS DENGAN TEKANAN DARAH PADA ANGGOTA PB UNMUH PONOROGO - Saiful Nurhidayat (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2019)
Physical activity in addition to dealing with heart rate, will cause an increase in blood pressure (Sulastri et al., 2012). Exercise or physical activity carried out regularly and regularly can turn a stressor into a stimulator. But if physical activity is done irregularly, the stressor will inhibit the homeostatic process in the body. The purpose of this study is to determine the relationship between the frequency of playing badminton and blood pressure in PB UNMUH Ponorogo members. The research will be conducted on PB UNMUH Ponorogo members, a representative sample of 33 respondents taken by Purposive Sampling. Quantitative design with Cross sectional design that studies the frequency of playing badminton and blood pressure. The instrument in this study used a questionnaire and observation sheet. Univariate analysis uses frequency distribution. Gamma Test to find out the relationship between the frequency of playing badminton and blood pressure. The results of the study showed that the majority of PB UNMUH Ponorogo's members of badminton played mostly (48.5%) or 16 people twice a week. Blood pressure of 39.4% or 13 respondents was normal. There is a relationship between the frequency of playing badminton with the incidence of hypertension in members of PB UNMUH Ponorogo with P = 0.020 (= 0.05). The closeness of the value (Value) is -0.452. It is expected that PB UNMUH Ponorogo members can do badminton training regularly and the intensity is adjusted to their respective abilities in order to achieve optimal fitness and avoid hypertension or other heart disease. Keywords: frequency of playing badminton, blood pressure.